2017
DOI: 10.3389/fnins.2017.00513
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Response to Intracortical Microelectrodes Is Not Altered with Dip-Coating of Polyethylene Glycol (PEG)

Abstract: Poly(ethylene glycol) (PEG) is a frequently used polymer for neural implants due to its biocompatible property. As a follow-up to our recent study that used PEG for stiffening flexible neural probes, we have evaluated the biological implications of using devices dip-coated with PEG for chronic neural implants. Mice (wild-type and CX3CR1-GFP) received bilateral implants within the sensorimotor cortex, one hemisphere with a PEG-coated probe and the other with a non-coated probe for 4 weeks. Quantitative analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…In the current study, the thiol-ene probe resulted in an increased inflammatory response, likely because of its greater surface area and vascular damage during implantation, consistent with previously published research ( Karumbaiah et al, 2013 ; Lee et al, 2017b ; Spencer et al, 2017 ). The thiol-ene materials utilized in the present study have previously undergone testing to control for material surface chemistry.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the thiol-ene probe resulted in an increased inflammatory response, likely because of its greater surface area and vascular damage during implantation, consistent with previously published research ( Karumbaiah et al, 2013 ; Lee et al, 2017b ; Spencer et al, 2017 ). The thiol-ene materials utilized in the present study have previously undergone testing to control for material surface chemistry.…”
Section: Discussionsupporting
confidence: 91%
“…This is the minimum size available on market although it is undoubted that a smaller size will cause less brain damage. Due to unique properties of biocompatibility and dissolvability in physiological environment, PEG is selected to fabricate the spheroid micropost . In our work, PEG 2000 was chosen for its lower melting point and faster dissolution rate than other polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, Lee found that coating planar silicon microelectrodes with polyethylene glycol (PEG) previously demonstrated no effect on the foreign body response [ 41 ]. Considering that PEG is highly hydrophilic, this is somewhat contradictory to the expected results.…”
Section: Discussionmentioning
confidence: 99%
“…Male Sprague Dawley rats (200–250 g, n = 11 per group) were implanted with either stiff silicon microelectrode probes dip-coated with shape memory polymer or size-matched bare silicon microelectrode probes. As performed previously by our group and others, microelectrode probes were implanted bilaterally (one in each hemisphere) and treated as independent of one another [ 41 , 42 ]. After implantation, animals were housed for 2 or 16 weeks, spanning the periods of initial and late-onset neurodegeneration [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%